Cigarette Smoke Reduces Fatty Acid Catabolism, Leading to Apoptosis in Lung Endothelial Cells: Implication for Pathogenesis of COPD - Gong, Jiannan; Zhao, Hui; Liu, Tanzhen; Li, Lifang; Cheng, Erjing; Zhi, Shuyin; Kong, Lufei; Yao, Hong-Wei; Li, Jianqiang (Frontiers in Pharmacology, 2019)
Endothelial cell (EC) apoptosis contributes to cigarette smoke (CS)-induced pulmonary emphysema. Metabolism of glucose, glutamine and fatty acid is dysregulated in patients with chronic obstructive pulmonary disease (COPD). Whether CS causes metabolic dysregulation in ECs, leading to development of COPD remains elusive. We hypothesized that CS alters metabolism, resulting in apoptosis in lung ECs. To test this hypothesis, we treated primary mouse pulmonary microvascular ECs (PMVECs) with CS extract (CSE), and employed PMVECs from healthy subjects and COPD patients. We found that mitochondrial respiration was reduced in CSE-treated PMVECs, and in PMVECs from COPD patients. Specifically, oxidation of fatty acids (FAO) was reduced in these cells, which linked to reduced carnitine palmitoyltransferase 1a (Cpt1a), an essential enzyme for carnitine shuttle. CSE-induced apoptosis was further increased when cells were treated with a specific Cpt1 inhibitor etomoxir or transfected with Cpt1a siRNA. L-carnitine treatment augmented FAO, but attenuated CSE-induced apoptosis by upregulating Cpt1a. CSE treatment increased palmitate-derived ceramide synthesis, which was reduced by L-carnitine. Although CSE treatment increased glycolysis, inhibiting glycolysis with 2-Deoxy-D-glucose had no effects on CSE-mediated apoptosis in lung ECs. Conclusively, FAO reduction increases ceramide and apoptosis in lung ECs treated with CSE, which may contribute to the pathogenesis of COPD/emphysema.